Ảnh hưởng của quản trị công ty đến mức độ công bố thông tin công cụ tài chính của ngân hàng thương mại tại Việt Nam - Nguyễn Thị Thu, Hiền (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
This study aims to measure the financial instrument disclosure (FID) level in Vietnam commercial banks and to investigate its relationship with corporate governance. The FID Index of 115 items was formed based on IFRS 7, Vietnam financial instrument disclosure requirements, and content analysis method. The authors use a sample of 299 bank-year observations for banks over the period 2010–2022.  This paper performs the F-test, Breusch-Pagan and Hausman test to identify the appropriate regression model. The findings indicate that the level of financial instrument disclosure provided by the sample banks is relatively low with only 48% of related items being supplied. This article employs regression analyses with the Generalized Least Squares (GLS) model to examine the impact of corporate governance characteristics on banks’ financial instrument disclosure levels. The findings show that this level has a statistical association with foreign ownership, role duality, and audit committee size.  However, the study fails to document its significant associations with board size, and board independence. This article contributes to the literature on the relationship between corporate governance and financial instrument disclosure, and adds evidence about the application of agency theory and signaling theory in accounting policy choice. Research results show that Vietnam should soon issue accounting standards for financial instruments. Banks should better monitor the disclosure of financial instrument information.
Keywords: Financial Instrument; Accounting; IFRS7; Corporate Governance; Commercial Bank